2021
DOI: 10.1051/e3sconf/202126602010
|View full text |Cite
|
Sign up to set email alerts
|

On the recycling and use of microsilica in the oil industry

Abstract: Cementing of casing strings is one of the most important processes of well construction for the exploration and exploitation of oil, gas and gas condensate fields. Despite more than half a century of research and development of grouting mortars, they are not able to provide high strength and good adhesion to the casing string. The article considers the possibility of using microsilica (waste of silicon production) in the oil industry, as an additive of a plugging solution to increase the strength, expansion va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…et al and Zimina, D.A. et al [69,70] have demonstrated the sensitivity of microsilica-modified concrete to temperature fluctuations during its hardening process. Under low temperatures, there is a decrease in the rate of hydration and strength enhancement, whereas elevated temperatures result in a sharp increase in these properties.…”
Section: Study Of Promising Methods For Processing and Recycling Wast...mentioning
confidence: 98%
See 3 more Smart Citations
“…et al and Zimina, D.A. et al [69,70] have demonstrated the sensitivity of microsilica-modified concrete to temperature fluctuations during its hardening process. Under low temperatures, there is a decrease in the rate of hydration and strength enhancement, whereas elevated temperatures result in a sharp increase in these properties.…”
Section: Study Of Promising Methods For Processing and Recycling Wast...mentioning
confidence: 98%
“…Under low temperatures, there is a decrease in the rate of hydration and strength enhancement, whereas elevated temperatures result in a sharp increase in these properties. An analysis of earlier studies [69,70] unveiled that the addition of microsilica significantly bolsters the strength of a concrete mix. The degree of strength augmentation is contingent on several variables, including the mix type, cement quality, microsilica quantity, water-soluble additive volume, filler characteristics, and curing conditions.…”
Section: Study Of Promising Methods For Processing and Recycling Wast...mentioning
confidence: 99%
See 2 more Smart Citations
“…Under the conditions of Tau-KenTemir LLP, when smelting one ton of technical silicon according to standard technology using vein quartz with a carbonaceous reducer, one ton of microsilica is captured by gas cleaning systems, with 65-70% extraction of silicon into metal [ [2], [3]]. Such average annual technical and economic indicators significantly worsen the economics of production, which not only highlights the problem of the lack of technological solutions for the processing/utilization of microsilica but also creates an environmental problem associated with the storage of technogenic waste [ [4], [5], [6], [7]]. This fact indicates the need for a number of research works to find a competent utilization of microsilica.…”
Section: Introductionmentioning
confidence: 99%